Cover Feature: Variations in the Solid‐State Emissions of Clothespin‐Shaped Binuclear trans‐Bis(salicylaldiminato)platinum(II) with Halogen Functionalities (Eur. J. Inorg. Chem. 31/2019). Issue 31 (7th August 2019) - Ikeshita, Masahiro; Ito, Mizuki; Naota, Takeshi
Abstract : The Cover Feature shows the contrasting emission properties of crystal polymorphs of a clothespin‐shaped bimetallic platinum(II) complex bearing iodine atoms. The polymorph with an interpenetrating alignment brought about by one‐dimensional infinite I⋯π interactions is less emissive, while the polymorph with a non‐interpenetrating alignment resulting from a two‐dimensional constraint network consisting of I⋯I and Pt⋯Pt interactions exhibits strong phosphorescence. More information can be found in the Full Paper by T. Naota et al.